Mutations in a new Streptomyces coelicolor locus which globally block antibiotic biosynthesis but not sporulation. - Adamidis, T (1990)
Streptomyces coelicolor produces four known antibiotics. To define genetic elements that regulate antibiotic synthesis, we screened for mutations that visibly blocked synthesis of the two pigmented antibiotics and found that the mutant strains which we recovered were of two classes--double mutants and mutants in which all four antibiotics were blocked. The mutations in these multiply blocked strains define a new locus of S. coelicolor which we have named absA. The genetic location of absA, at 10 o'clock, is distinct from the locations of the antibiotic gene clusters and from other known mutations that affect antibiotic synthesis. The phenotype of the absA mutants suggests that all S. coelicolor antibiotic synthesis genes are subject to a common global regulation that is at least in part distinct from sporulation and that absA is a genetic component of the regulatory mechanism.